Pretiree lifestyles in relation to musculoskeletal health: cross‐sectional data from the Geelong Osteoporosis Study. Issue 2 (1st July 2018) - Pasco, Julie A.; Holloway‐Kew, Kara L; Hyde, Natalie K; Tembo, Monica C; Rufus, Pamela G; Sui, Sophia X; Berk, Michael; Kotowicz, Mark A
Abstract: Aims: What happens in the early‐elderly 'pretiree' period potentially influences the divergent paths of healthy or unhealthy ageing. In this cross‐sectional study, we aimed to profile musculoskeletal health and lifestyle behaviours for men and women in their late‐fifties and sixties. Methods and results: For 482 participants from the Geelong Osteoporosis Study, we measured DXA‐derived relative appendicular lean mass (rALM), bone mineral density (BMD) at the femoral neck and percentage body fat mass (%BF). Low‐rALM and low‐BMD referred to sex‐specific T‐scores<‐1.0. Associations between exposures and low‐rALM and/or low‐BMD were explored using multivariable logistic regression. Three‐quarters of participants had high %BF, 98(20.3%) had low‐rALM, 202(41.9%) had low‐BMD and 63(13.1%) had both low‐rALM and low‐BMD. Eight‐two (17.0%) were very active and one‐third participated in sports/recreational activities. Most [n=416(87.8%)] met the recommended daily intake (RDI) for protein; only 119(25.1%) met the RDI for calcium. Less than 10% smoked and one‐third exceeded recommended alcohol intakes. Independent of age, weight and sex, greater %BF and sedentary behaviour increased the likelihood of low‐rALM; high‐alcohol consumption increased the likelihood of low‐BMD; and greater %BF increased the likelihood of low‐rALM and low‐BMD combined. Conclusions: One‐half of participants had rALM and BMD in the normal range. Only a few were involved in resistance‐training or weight‐bearing exercise, despite having the capacity to be physically active. As sedentary lifestyles, excessive adiposity and high alcohol use were associated with low‐rALM and/or low‐BMD, we propose that these adverse factors be potential targets among pretirees to minimise their risk of entering old age with poor musculoskeletal health.